Expanding Understanding of Cyber Incidents : Why alternatives for the Law of Armed Conflict are needed - Karppinen, Erica (fi=Turun yliopisto|en=University of Turku|, 2018)
Cyber incidents are a growing menace for states and individuals alike. Even though they have been around for quite some time, the international legal governance of the cyber operations remains insufficient. There is currently no specific international legal regime in place, partly due to the presumed applicability of the Law of Armed Conflict. Such rhetoric that bears a meaning within the pre-existing international law governing armed conflicts is often employed when cyber operations are being discussed. However, the cyberspace as an environment differs from that of the kinetic world, thus posing challenges for the analogous application of the rhetoric and principles presented by the Law of Armed Conflict. There have been regulatory attempts to govern the cyberspace, but these attempts have failed to carefully take into consideration the characteristics of the cyberspace, to which precedents from the kinetic world may not be found. The increase in the civilian participation to matters previously considered to be in the sole governance of the states poses a further challenge to the legal governance of the cyber operations. Thus, the part non-state parties play in cyber operations, be it knowingly or unknowingly, must be reflected in the international legal regime that governs them. This includes the participation of the non-state parties responsible for the cyber governance. The great extent to which cyber operations differentiate from conventional, kinetic operations suggests that alternatives for the Law of Armed Conflict must be sought in the international legal governance of cyber operations, likely in the form of a new, international legal regime that could be drafted via a multi-stakeholder initiative.